2006
DOI: 10.1261/rna.213906
|View full text |Cite
|
Sign up to set email alerts
|

The abundance of the spliceosomal snRNPs is not limiting the splicing of U12-type introns

Abstract: The rate of excision of U12-type introns has been reported to be slower than that of U2-type introns, suggesting a rate-limiting bottleneck that could down-regulate genes containing U12-type introns. The mechanistic reasons for this slower rate of intron excision are not known, but lower abundance of the U12-type snRNPs and slower rate of assembly or catalytic activity have been suggested. To investigate snRNP abundance we concentrated on the U4atac snRNA, which is the least abundant of the U12-type snRNAs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
6
33
0
Order By: Relevance
“…However, as snRNPs are present in large excess in the cell, it is unlikely that a 50% reduction in di-snRNP levels alone would cause the observed effects. Indeed, residual amounts (Ͻ20%) of U4atac snRNA are sufficient to support the splicing of endogenous pre-mRNAs at WT levels (25), suggesting that the reduction of a single spliceosomal component by 80 to 90% does not a priori lead to splicing inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as snRNPs are present in large excess in the cell, it is unlikely that a 50% reduction in di-snRNP levels alone would cause the observed effects. Indeed, residual amounts (Ͻ20%) of U4atac snRNA are sufficient to support the splicing of endogenous pre-mRNAs at WT levels (25), suggesting that the reduction of a single spliceosomal component by 80 to 90% does not a priori lead to splicing inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, based on the migration behavior of the 48K protein on polyacrylamide gels, it was previously suggested that the protein may be posttranslationally modified (38). The excision of U12-type introns appears to be the ratelimiting step in the splicing of genes containing both types of introns (23,25). Therefore, the posttranslational modification of unique spliceosomal factors, such as 48K, may potentially allow for the rapid regulation of the U12-dependent spliceosome and thus affect the expression of genes with U12-type introns.…”
Section: Discussionmentioning
confidence: 99%
“…A key characteristic of U12-type introns is that they are removed more slowly than U2-type introns, suggesting they may serve as rate-limiting controls for the expression of their host genes (35,36). The slow processing rate of the U12-dependent spliceosome was suggested by König et al (23) to lead to the export of unspliced pre-mRNAs from the nucleus and entail the need for splicing activity in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The subcellular localization of U1, U2, U6, U11, U12, U4atac, and U6atac snRNAs in several embryonic mouse tissues was analyzed by nonradioactive cRNA ISH on tissue sections. Sagittal sections of E15 NMRI mouse embryos were fixed in 4% paraformaldehyde, embedded in paraffin, and serially sectioned at 5 m. cRNA probes were labeled with DIG by performing in vitro transcription of snRNA clones (5,36) in the presence of DIG RNA labeling mix (Roche). Sense probes were synthesized from the complementary strand of the probe templates.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Another difference is that minor introns have been reported to be spliced more slowly, both in vitro 13,14 and also in vivo. [15][16][17][18] The slower splicing in vivo has been inferred from the elevated levels of unspliced U12-type introns in the cellular steady-state RNA pool. On average, U12-type introns show approximately 2-fold higher retention levels compared to the U2-type introns in the same gene.…”
Section: Introductionmentioning
confidence: 99%